Novel exploration of the presence and morphological features Spirometra (Cestoda: Diphyllobothriidae) in Javan spitting cobra snakes (Naja sputatrix) in Sidoarjo, Indonesia - RYANKA EDILA; MUSTOFA HELMI EFFENDI; LUCIA TRI SUWANTI; HYUCK-KEUN KWON; NNABUIFE BERNARD AGUMAH (Society for Indonesian Biodiversity, 2024)
Abstract. Edila R, Effendi MH, Suwanti LT, Kwon H-K, Agumah NB. 2024. Novel exploration of the presence and morphological features Spirometra (Cestoda: Diphyllobothriidae) in Javan spitting cobra snakes (Naja sputatrix) in Sidoarjo, Indonesia. Biodiversitas 25: 3318-3324. The study aimed to investigate the presence of spargana infection and provide a detailed description of the morphology, morphometry and histology in Javan spitting cobra snakes (Naja sputatrix Boie 1827) from Sidoarjo, Indonesia. Ethical approval was obtained and 51 living wild-caught N. sputatrix were collected from local sellers. All samples were euthanized and observed for the presence of plerocercoid. Identification of the plerocercoid as the larval infective stage was made using a carmine staining method drawn by using a camera lucida and routine histological study using hematoxylin-eosin staining. The positive rate of snakes in this study was 54.9%. A total of 165 spargana were collected which divided 82(49.6%) infecting muscles, 31 (16.7%) in viscera and 52 (31.5%) located in subcutaneous tissues. The plerocercoid length and width were 50-95 mm and 1.42-1.81 mm. Morphological analysis confirmed Spirometra characteristics and histological sections provided insights into spargana's structural complexity. This study represents the first detailed exploration of the morphological features, morphometry, and histology of Spirometra plerocercoids in Indonesia. The high prevalence of spargana in N. sputatrix underscores the importance of improving epidemiological databases, stringent wildlife trade regulations, and awareness programs to prevent sparganosis in Indonesia.